Folklore, erudition and empiricism in 16th century Spain. An example in Cervantes' Persiles - Marchante Aragón, Lucas (Íkala, Revista de Lenguaje y Cultura, 2007)
Pero Mexía’s Silva de varia lección, Antonio de Torquemada’s Jardín de fl ores curiosas n de flores curiosas, and Juan Huarte de San Juan’s Examen de ingenios, are works for the diffusion of knowledge which illustrate the debate surrounding forms of explaining reality in sixteenth and seventeenth century Spain. At times verbally violent, the inter-textual dialogue between these examples of epistemologically opposing tendencies—the bookish, the folkloric, and the empirical—that fought to overcome one another in the offi cial discourse, fi nds itself re-enacted in another dialogue that discusses a marvelous event within Cervantes’ Persiles. As in the famous purge of Don Quixote’s library, this dialogue becomes another scrutiny, not literary, but about the explanation of the natural world and supernatural phenomena. Received: 09-04-07 / Accepted: 13-07-07 How to reference this article: Marchante Aragón, L. (2007). Folclore, erudición y empirismo en la España del siglo XVI: un ejemplo en Persiles de Cervantes. Íkala. 12(1), pp. 97 – 117.